Miriades methodology guide - Cot, Michel; Emperaire, Laure; Henry, Isabelle; Laplaze, Laurent; Roubaud, François; Sylvestre, Florence; Vidal, Laurent; Zucker, Jean-Daniel (IRD Éditions, 2024)
The Miriades guide (multidimensional analysis of the impact of research and its innovations on the development of societies in the South) is intended as a methodological tool for researchers working in partnership with countries in the South and wishing to analyse the societal impact of their work. It was conceived by taking into account the methods developed by other research organisations and adapted to the particularities of the IRD's partnership research approach by the methodological group set up within the IRD, then adjusted after a pilot phase of Miriades.